The Concept of "Sex" and "Gender" in Psychology - T. B. Norimbetov; D. S. Yusupov (International Journal on Integrated Education, 2021)
In the modern process of teaching students of a higher educational institution, it is necessary to study them in some terms of psychological knowledge. Although these terms are not often used in teaching students, they need to distinguish between the philosophical-methodological and scientific-practical meaning of these terms. These terms are "sex" and "gender". The distinction between these terms is very important for university students.